BAGAIMANA MENGADOPSI KONSEP MANAJEMEN UNTUK MENGATUR PERILAKU KELUARGA: KONSEP MANAJEMEN ISLAM - Nailuvary, Henny (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
How do we deal with developing family life dynamics in the modern era through transforming Islamic management concepts? The cult that organizes family life through traditional theories and practices has experienced a culmination phase. This condition challenges modern society to carry out developments that are juxtaposed with management theory. This is an alternative to face the flow of modernity, which, on the one hand, is a challenge for Muslim society. The outdated concept of the traditional family is an obstacle to the development of modern society. Marriage is a noble business that has a lifelong contract. Therefore, the author hypothesizes that families who understand excellent and structured management will find it easier to face problems and find solutions. To answer these problems, the author uses a qualitative approach with the bibliometric analysis method. This framework aims to find research gaps related to the scientific discourse on family management in Islam and society. Management theory is a framework to analyze the research question trough bibliometric analysis. This study found that three main management concepts, business management, risk, and conflict, are an alternative to facing the challenges of dynamics and building relationships and social strata in modern families. Three of management type can use to face all challenges in modern era. Modern family easily use these ways to build the robustness family and to organize all instrument among them. Keywords: Family Management, Islamic Management Concept, Modern Civilization